Desempenho zootécnico de juvenis de Pomacea haustrum (Revee, 1856) (Mollusca: Gastropoda: Ampullariidae), mantidos em diferentes dietas e salinidades - Rodrigues, Lucas Cipriano (2019)
Considering the current scenario in evidence of demand for alternative sources of food in the world, the cultivation of species normally considered as unconventional, is shown as an alternative to minimize the scarcity of food making the theme relevant. The present work had as objective to evaluate if the supply of different diets derived from commercial diets and the developmentin different salinities of juveniles of Pomaceahaustrumwould result in different zootechnicalperformances. After the hatching of 7 spawnings of P.haustrum, in the laboratory, the juveniles were randomly selected and transferred to the culture vessels. Two different rations were provided: a commercial feed containing a greater amount of ingredients rich in crude protein of vegetable origin (rabbit ration) and a commercial ration containing a balanced amount of crude protein rich ingredients of vegetal and animal origin (PM ) (dog food). The animals were stored at different salinities (0, 2 and 4) parts per thousand(ppt). The experiment lasted 65days. The water quality parameters analyzed (temperature, dissolved oxygen and pH) remained within the ideal range for all treatments, with average 25°C, 8,6 mg/L and 7,1, respectively. At salinity of 4ppt there was 100% mortality after 21 hours. The snails that were fed the PM diet compared to the PV in fresh water (0 ppt) showed a trend of better zootechnical results (final mean weight, weight gain, final mean growth, specific growth rate, protein efficiency and apparent feed conversion) despite of statistical difference (p>0,05). There was significant divergence (p≤0,05) between the results of zootechnical performance (final mean weight, weight gain, final mean growth, specific growth rate, protein efficiency and apparent feed conversion) of individuals cultivated in freshwater and salinity of 2ppt, regardless of the protein origin of the feed. Therefore, the protein origin of the feed did not significantly influence the performance of the cultured animals, while the salinity of the water impaired the development of the cultured animals directly proportional to its concentration.